Comparative Analysis Of The Decorated Arraies With Geometric And Plant Motifs In Architecture Of The Grand Mosque Of Yazd And Their Developments - Hanifi, Mona Abdullahi; Maleki, Arian (The Turkish Online Journal of Design Art and Communication, 2016)
The decorations used in traditional and Islamic arts have always had a special place. These decorations in a way reflect the ideas of the artists, the customs and traditions of each region. The expression of these ideas happens in such a way that they are not separated from each other, but we see the effects of one over the other in various arts. In the meantime, Yazd region, in turn, has been the scene of various arts which have been formed together with the impact of specific thoughts of the region. One of the distinctive features of Islamic art are its decorations that reaches its peak at a certain stage of development and becomes especially important, as each has an effect on the others and some sparks of this effect is evident in the samples of art. This issue can be significantly observed in the artwork a certain area whose artists have the same ideas. The architectural decorations in various parts of the country, especially in desert areas are of particular importance and are directly related with attitudes and needs. That's why the mosque in Yazd, Yazd is one of the oldest examples of religious architecture with a variety of geometric and plant tiling with beautiful and unique structural and decorative elements of the array. Thus, the present study study is a comparative analysis of the decorated arraies with geometric and plant designs in architecture of the Grand Mosque of Yazd and their developments. This study with historical analysis method examines the historical documents, bibliographical resources and field studies to collect data, and after analysis and summarizing, it is concludes about the changes in the method of implementation (the Brick molding and color Tile) and a form of semantic content (natural plant motifs and arabesques and complex geometric shapes). Further, the decorative structure changes with calligraphic lines used in the mosque is used in the course of their analysis.
Keywords: Decorative array; Islamic architecture; geometric and plant motifs; Yazd Great mosque; kiremitli Dekoratif dizi; İslam mimarisi; geometrik ve bitkisel motifler; Yazd Büyük cami